A Systematic Literature Review of Islamic Boarding School (Pesantren) Education in Indonesia (2014-2024) - Muhamad Arif; Sulaiman Dorloh; Shuhairimi Abdullah (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2024)
During its development, Islamic boarding schools carried out educational transformation by compromising with the establishment of formal education and integrating religious knowledge and science. Apart from that, Islamic boarding schools are experiencing rapid development, one of which is the existence of virtual Islamic boarding schools. The research method used is a systematic literature review (SLR). In the literature selection process, researchers apply five provisions, first; The papers that were analyzed were only papers from journal articles (published), not including book reviews, conferences, proceedings, theses, and dissertations. Second, the selection of articles is limited to the last ten years 2014-2024. Third, the database used in the article search process is a global database, namely Scopus and Taylor and Francis. Fourth, at the article search stage, researchers use third-party applications, namely publish or publish and visualize using Vos Viewer. Fifth, in the search the keywords used were limited to English, because researchers wanted to get complete data about Islamic boarding school (Pesantren) education in Indonesia. The research findings are that the Islamic boarding school (Pesantren) model that is widely developed in Indonesia consists of three models, namely Salaf/traditional, modern, and integrated. First, the characteristics of Salaf (traditional) Islamic boarding schools, Islamic boarding schools only have non-formal education and are very identical to learning sourced from books. yellow. secondly, the characteristics of a modern Islamic boarding school (Pesantren)are Islamic boarding schools that use a modern approach, such as the curriculum and learning process. modern Islamic boarding school (Pesantren) education implements formal education (schools according to government regulations) and non-formal education (Islamic boarding schools). third, integrated Islamic boarding school, an Islamic boarding school (Pesantren)that combines Salaf and modern Islamic boarding school (Pesantren) education, so that the elements contained therein run collaboratively, such as a curriculum that combines the national curriculum and Islamic boarding school (Pesantren) curriculum, so that the Yellow Book becomes the main requirement for learning.